Pengaruh Pemberian Kompres Daun Dadap Serep Untuk Menurunkan Panas Bayi Setelah Imunisasi DPT (Difteri, Pertusis, Tetanus) - Vanessa Rasti; Kristina Maharani; Qomariyah Qomariyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Fever is a common side effect after infants receive DPT (Diphtheria, Pertussis, and Tetanus) immunization. This condition often causes concern for parents, so appropriate treatment is needed. Generally, fever can be treated with pharmacological and non-pharmacological methods. One of the most widely used non-pharmacological treatments is warm compresses. However, innovations in the use of natural ingredients are starting to be noticed, one of which is dadap serep leaves which are thought to be more effective in helping to lower body temperature. The active compounds in dadap serep leaves are believed to provide a calming effect while helping vasodilation, so that body heat can be reduced more quickly. Methodology: This study used a quantitative method with a quasi-experimental design of the non-equivalent pretest posttest control group design. The research subjects were divided into two groups, namely the intervention group who received dadap serep leaf compresses and the control group who received warm compresses. Body temperature measurements were taken before and after the intervention. The data obtained were analyzed using statistical tests to see the difference in temperature reduction in each group. Results: The intervention group showed a significant reduction in body temperature, namely 73.3%. In contrast, the control group using warm compresses only experienced a 20% reduction, which was not statistically significant. The results of the intergroup comparison test also showed a significant difference, supporting the research hypothesis. Conclusion: Dadap serep leaf compresses were proven to be more effective than warm compresses in reducing fever in infants following DPT immunization. These findings suggest that the use of dadap serep leaves can be recommended as a safe, effective, and easy-to-implement non-pharmacological intervention alternative in daily practice.